2015
DOI: 10.1159/000371521
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Role of Having Confidant on the Development of Alzheimer's Disease in a Community-Based Cohort of Older People in Brazil

Abstract: Background: Social interaction is a lifestyle factor associated with a decreased risk of dementia in several studies. However, specific aspects of these social factors influencing dementia are unknown. This study aimed at evaluating the role of the distinct aspects of social support on the incidence of dementia in acommunity-based cohort of older people in Brazil. Methods: A total of 345 healthy and independent elderly subjects living in the community were followed by 12 years. Incident cases of dementia and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Fifteen studies examined prospectively or retrospectively collected time-varying exposures: social support [ 106 ]; social strain [ 93 ]; formal and informal social activity participation [ 32 , 42 , 51 , 56 , 67 , 83 , 84 , 87 , 96 , 107 , 143 ] social network structure (e.g., number of family/friends) [ 32 , 79 , 83 ]; participation in national health insurance [ 67 ]; having a confidante at earlier ages [ 102 ]; and income inequality [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies examined prospectively or retrospectively collected time-varying exposures: social support [ 106 ]; social strain [ 93 ]; formal and informal social activity participation [ 32 , 42 , 51 , 56 , 67 , 83 , 84 , 87 , 96 , 107 , 143 ] social network structure (e.g., number of family/friends) [ 32 , 79 , 83 ]; participation in national health insurance [ 67 ]; having a confidante at earlier ages [ 102 ]; and income inequality [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…6,[8][9][10]12,28 Although no prior work has focused on evaluating the association of having a confidant with cognitive outcomes, other studies have found an association with other health outcomes, such as mortality due to coronary artery disease and dementia. 23,24 In addition, confidants are an especially important source of support for older adults and may thus be particularly relevant for cognition. Prior work has shown that social support is associated with both better cognitive function at baseline and at follow-up and that having a confidant is the primary source of both emotional and instrumental support.…”
Section: Discussionmentioning
confidence: 99%
“…Participants who reported having no children, no relatives, or no friends also received a score of 0 for the respective measure. Given prior evidence that having a confidant might be of special relevance for both emotional and instrumental support, 19,20 as well as for other health outcomes such as mortality due to coronary artery disease and dementia, 23,24 we also evaluated this indicator as a primary exposure. Having a confidant was coded as a binary variable (1 if participant reported having a confidant that he or she sees daily and 0 otherwise).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Amieva et al found that feeling satisfied with social interactions and perceived reciprocity was protective of dementia over 15 years, but the size and nature of social networks was not associated with dementia risk. Furthermore, having a confidant was found to be protective of dementia in a 12‐year cohort study . Of note, neither of these studies measured loneliness, but one could assume that feeling satisfied with social interactions and having a confidant could reduce feelings of loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, having a confidant was found to be protective of dementia in a 12-year cohort study. 18 Of note, neither of these studies measured loneliness, but one could assume that feeling satisfied with social interactions and having a confidant could reduce feelings of loneliness.…”
Section: Introductionmentioning
confidence: 99%